Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 46569 by scientist last updated on 28/Oct/18

show that  If a^2 ,b^2 ,c^(2 )  are in A.P  the cotA,cotB,cotC are  also in A.P

$${show}\:{that}\:\:{If}\:{a}^{\mathrm{2}} ,{b}^{\mathrm{2}} ,{c}^{\mathrm{2}\:} \:{are}\:{in}\:{A}.{P}\:\:{the}\:{cotA},{cotB},{cotC}\:{are} \\ $$$${also}\:{in}\:{A}.{P} \\ $$

Answered by tanmay.chaudhury50@gmail.com last updated on 28/Oct/18

((sinA)/a)=((sinB)/b)=((sinc)/c)=k(say)  cotA=((cosA)/(sinA))=(((b^2 +c^2 −a^2 )/(2bc))/(ak))=((b^2 +c^2 −a^2 )/(2abck))  cotB=((a^2 +c^2 −b^2 )/(2abck))  cotC=((a^2 +b^2 −c^2 )/(2abck))  to prove 2cotB=cotA+cotC  LHS  2×((a^2 +c^2 −b^2 )/(2abck))=2×((2b^2 −b^2 )/(2abck))=((2b^2 )/(2abck))=(b/(ack))  since 2b^2 =a^2 +c^2    a^2 ,b^2 ,c^2  are in A.P  now  cotA+cotC  ((b^2 +c^2 −a^2 )/(2abck))+((a^2 +b^2 −c^2 )/(2abck))  =((2b^2 )/(2abck))=(b/(ack))  hence LHS=RHS  so cotA , cotB,  cotC are inAP  proved

$$\frac{{sinA}}{{a}}=\frac{{sinB}}{{b}}=\frac{{sinc}}{{c}}={k}\left({say}\right) \\ $$$${cotA}=\frac{{cosA}}{{sinA}}=\frac{\frac{{b}^{\mathrm{2}} +{c}^{\mathrm{2}} −{a}^{\mathrm{2}} }{\mathrm{2}{bc}}}{{ak}}=\frac{{b}^{\mathrm{2}} +{c}^{\mathrm{2}} −{a}^{\mathrm{2}} }{\mathrm{2}{abck}} \\ $$$${cotB}=\frac{{a}^{\mathrm{2}} +{c}^{\mathrm{2}} −{b}^{\mathrm{2}} }{\mathrm{2}{abck}} \\ $$$${cotC}=\frac{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{c}^{\mathrm{2}} }{\mathrm{2}{abck}} \\ $$$${to}\:{prove}\:\mathrm{2}{cotB}={cotA}+{cotC} \\ $$$${LHS} \\ $$$$\mathrm{2}×\frac{{a}^{\mathrm{2}} +{c}^{\mathrm{2}} −{b}^{\mathrm{2}} }{\mathrm{2}{abck}}=\mathrm{2}×\frac{\mathrm{2}{b}^{\mathrm{2}} −{b}^{\mathrm{2}} }{\mathrm{2}{abck}}=\frac{\mathrm{2}{b}^{\mathrm{2}} }{\mathrm{2}{abck}}=\frac{{b}}{{ack}} \\ $$$${since}\:\mathrm{2}{b}^{\mathrm{2}} ={a}^{\mathrm{2}} +{c}^{\mathrm{2}} \:\:\:{a}^{\mathrm{2}} ,{b}^{\mathrm{2}} ,{c}^{\mathrm{2}} \:{are}\:{in}\:{A}.{P} \\ $$$${now} \\ $$$${cotA}+{cotC} \\ $$$$\frac{{b}^{\mathrm{2}} +{c}^{\mathrm{2}} −{a}^{\mathrm{2}} }{\mathrm{2}{abck}}+\frac{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{c}^{\mathrm{2}} }{\mathrm{2}{abck}} \\ $$$$=\frac{\mathrm{2}{b}^{\mathrm{2}} }{\mathrm{2}{abck}}=\frac{{b}}{{ack}} \\ $$$${hence}\:{LHS}={RHS} \\ $$$${so}\:{cotA}\:,\:{cotB},\:\:{cotC}\:{are}\:{inAP}\:\:{proved} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com